High-performance polarization control modulated surface plasmon resonance sensor based on monolayer graphene/Au-NPs architecture for detection of DNA hybridization. (16th September 2019) - Sun, Yi; Cai, Haoyuan; Qiao, Xin; Wang, Xiaoping
Abstract: A highly sensitive polarization control modulated plasmonic biosensor based on monolayer graphene/Au-NPs for direct detection of single-stranded DNA (ssDNA) hybridization is reported. The presence of monolayer graphene on gold film provides novel functionalized derivatives through π -stacking interactions. In addition, the online assembly strategy via in situ monitoring between ssDNA and Au-NPs makes the binding easier and quantifiable. The use of strong plasmon-mediated energy confinements induces an approximately 30-fold intense field enhancement of the reflected light. The architecture exhibits a linear dynamic range of 10 −15 to 10 −7 M for the detection of target ssDNA. Moreover, the new biosensor can achieve an ultralow detection limit of 500 aM for 23-mer ssDNA via improved sensitivity to molecular bindings.